A Review on Chemical versus Microbial Leaching of Electronic Wastes with Emphasis on Base Metals Dissolution - Srabani Mishra (MDPI AG, 2021)
There is a growing interest in electronic wastes (e-wastes) recycling for metal recovery because the fast depletion of worldwide reserves for primary resources is gradually becoming a matter of concern. E-wastes contain metals with a concentration higher than that present in the primary ores, which renders them as an apt resource for metal recovery. Owing to such aspects, research is progressing well to address several issues related to e-waste recycling for metal recovery through both chemical and biological routes. Base metals, for example, Cu, Ni, Zn, Al, etc., can be easily leached out through the typical chemical (with higher kinetics) and microbial (with eco-friendly benefits) routes under ambient temperature conditions in contrast to other metals. This feature makes them the most suitable candidates to be targeted primarily for metal leaching from these waste streams. Hence, the current piece of review aims at providing updated information pertinent to e-waste recycling through chemical and microbial treatment methods. Individual process routes are compared and reviewed with focus on non-ferrous metal leaching (with particular emphasis on base metals dissolution) from some selected e-waste streams. Future outlooks are discussed on the suitability of these two important extractive metallurgical routes for e-waste recycling at a scale-up level along with concluding remarks.